TRANSPLANTASI KARANG BATU BERCABANG DI PERAIRAN TANJUNG PAPUTUNGAN - Carolus Paulus Paruntu; Febrianto Mudul; Kakaskasen A. Roeroe; Medy Ompi; Sandra O. Tilaar; Adnan S. Wantasen (Sam Ratulangi University, 2023)
The formation of coral reefs is a long and complex process. The process of forming coral reefs begins with the attachment of various lime-producing biota on a hard substrate. Coral reefs take quite a long time to recover and are highly dependent on water conditions. Until now, pressures caused by human activities such as pollution from land and destructive fisheries practices have been considered a major threat to coral reefs. Efforts to overcome damage to coral reef ecosystems can be done by developing coral transplantation techniques. In response to this, the research wiil apply the method of artificial reefs from concrete blocks as a container for the installation of colonies of Acropora formosa spesies and Porites cylindrica spesies. A total of 75 branched coral colonies were transplanted in the waters of 75 branched coral colonies were transplanted in the waters of the Paputungan cape 39 colonies of branched growth forms of Acropora form and 36 colonies of branched grotwth forms of Porites cylindrica spesies were transplanted in artificial reef units. Data collection in the field in the form colonies that were successfully transplanted into artificial reef units totaling 6 units will be documented using cameras from each block taken perpendicular pictures and photographing colonies from earch artificial reef unit. The results of the shoot were then analyzed using software of the Image-J application. At the end of the observation process, it was found that the highest resistence of transplane colonies was 97.2 % where there were 35 surviving colonies and 1 dead colony out of a total of 36 colonies transplanted by Porites cylindrica spesies. Meanwhile, observations found that the lowest resistnce of transplant colonies that survived and 13 colonies that died out of a total of 39 colonies transplanted by acropora formosa spesies. Acropora formosa has a relatively fast increase compared to Porites cylindrica spesies. The highest accretion was dominated by the 18.05 mm fragment-size Acropora formosa spesies at the end of the sixth lunar observation.Keywords: Restoration, transplantation, Branching Coral, Tanjung Paputungan, North Minahasa ABSTRAKTerbentuknya terumbu karang merupakan suatu proses yang lama dan kompleks. Proses terbentuknya terumbu karang dimulai dengan penempelan berbagai biota penghasil kapur pada substrat yang keras. Terumbu karang membutuhkan waktu yang cukup lama untuk pulih kembali dan sangat tergantung dari kondisi perairan. Hingga kini, tekanan yang disebabkan oleh kegiatan manusia seperti pencemaran dari daratan dan praktek perikanan yang merusak telah dianggap sebagai ancaman utama untuk terumbu karang. Upaya penanggulangan kerusakan ekosistem terumbu karang dapat dilakukan dengan menggembangkan teknik transplantasi karang (coral transplantation). Menanggapi hal tersebut, maka dalam penelitian kali akan menerapkan metode terumbu buatan dari blok beton sebagai wadah untuk pemasangan koloni spesies Acropora formosa dan spesies Porites cylindrica. Sebanyak 75 koloni karang bercabang yang di transplantasi di perairan tanjung Paputungan 39 koloni bentuk pertumbuhan bercabang spesies Acropora formosa dan 36 koloni bentuk pertumbuhan bercabang spesies Porites cylindrica ditransplantasikan pada unit terumbu buatan. Pengambilan data dilapangan berupa Koloni yang berhasil di transplantasi ke unit terumbu buatan berjumlah 6 unit akan didokumentasikan menggunakan kamera dari tiap-tiap blok di ambil gambar tegak lurus dan memotret koloni dari masing-masing unit terumbu buatan. Hasil pemotretan tersebut selanjutnya dianalisa menggunakan sofware atau aplikasi Image-J. Akhir proses pengamatan ditemukan bahwa ketahanan koloni transplan tertinggi yaitu 97,2 % dimana terdapat 35 koloni yang bertahan hidup dan 1 koloni yang mati dari total 36 koloni yang di transplantasi spesies Porites cylindrica. Sedangkan pengamatan ditemukan bahwa ketahanan koloni transplan terendah yaitu 66,6 % dimana terdapat 26 koloni yang bertahan hidup dan 13 koloni yang mati dari total 39 koloni yang di transplantasi spesies Acropora formosa. Acropora formosa mempunyai pertambahan relatif cepat di bandingkan janis Porites cylindrica. Pertambahan paling tinggi didominasi oleh spesies Acropora formosa ukuran fragmen 18,05 mm di akhir pengamatan bulan keenam.Kata Kunci: Restorasi, Transplantasi, Karang bercabang, Tanjung Paputungan, Minahasa Utara